2004
DOI: 10.1093/brain/awh165
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates associated with impaired disgust processing in pre-symptomatic Huntington's disease

Abstract: Disturbances in recognizing facial expressions of disgust have been reported previously in pre-symptomatic and manifest Huntington's disease. Given the substantial role of the insula and basal ganglia in the perception of disgust as revealed by functional imaging, lesion studies and intracerebral recordings, we propose dysfunction within the insula and/or basal ganglia as the underlying neural substrate. Using functional MRI (fMRI), we studied a group of nine pre-symptomatic Huntington's disease gene carriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
93
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 45 publications
15
93
0
1
Order By: Relevance
“…This provides a replication of previous research reporting poorer recognition accuracy for disgust in HD (e.g., Hennenlotter et al, 2004, Montagne et al, 2006, Sprengelmeyer et al, 1996. However, as impairment to angry faces was also observed, the present study does not support the notion that disgust (or the neural processes subserving its recognition) is qualitatively different to other negative emotions, but accords well with recent studies reporting deficits in other negative emotion processing (specifically anger).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This provides a replication of previous research reporting poorer recognition accuracy for disgust in HD (e.g., Hennenlotter et al, 2004, Montagne et al, 2006, Sprengelmeyer et al, 1996. However, as impairment to angry faces was also observed, the present study does not support the notion that disgust (or the neural processes subserving its recognition) is qualitatively different to other negative emotions, but accords well with recent studies reporting deficits in other negative emotion processing (specifically anger).…”
Section: Discussionsupporting
confidence: 87%
“…Other published studies have reported similar findings in HD (Hennenlotter et al, 2004, Montagne et al, 2006. However, studies with differing findings questioned the degree of impairment for disgust and implicated a universal deficit across basic negative emotions, primarily anger and fear (Calder et al, 2010, Henley et al, 2008, Milders et al, 2003, Snowden et al, 2008.…”
Section: Introductionmentioning
confidence: 56%
“…1 However, before the occurrence of motor symptoms, deficits in cognitive and affective processing have been observed in gene carriers. 2,3 Impairments in cognitive performance concern functions such as attention, memory and visuo-spatial processing. 4 These dysfunctions are already present in individuals who carry the gene mutation but display no overt motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found a disproportionately severe deficit in disgust recognition in the pre-symptomatic (Gray, Young, Barker, Curtis, & Gibson, 1997;Hennenlotter, et al, 2004;Sprengelmeyer, et al, 2006) and symptomatic stages of the disorder Sprengelmeyer, et al, 1996;Wang, Hoosain, Yang, Meng, & Wang, 2003), and there are findings indicating that the experience of disgust itself can also be affected (Hayes, Stevenson, & Coltheart, 2007;Mitchell, Heims, Neville, & Rickards, 2005). In these studies, however, the disproportionately severe deficit with disgust is mostly found within the context of more widespread problems in emotion recognition, and especially recognition of anger (Calder, et al, 2010).…”
Section: Introductionmentioning
confidence: 98%